x(x-17)-18x=(x-3)(x+15)

Simple and best practice solution for x(x-17)-18x=(x-3)(x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-17)-18x=(x-3)(x+15) equation:



x(x-17)-18x=(x-3)(x+15)
We move all terms to the left:
x(x-17)-18x-((x-3)(x+15))=0
We add all the numbers together, and all the variables
-18x+x(x-17)-((x-3)(x+15))=0
We multiply parentheses
x^2-18x-17x-((x-3)(x+15))=0
We multiply parentheses ..
x^2-((+x^2+15x-3x-45))-18x-17x=0
We calculate terms in parentheses: -((+x^2+15x-3x-45)), so:
(+x^2+15x-3x-45)
We get rid of parentheses
x^2+15x-3x-45
We add all the numbers together, and all the variables
x^2+12x-45
Back to the equation:
-(x^2+12x-45)
We add all the numbers together, and all the variables
x^2-35x-(x^2+12x-45)=0
We get rid of parentheses
x^2-x^2-35x-12x+45=0
We add all the numbers together, and all the variables
-47x+45=0
We move all terms containing x to the left, all other terms to the right
-47x=-45
x=-45/-47
x=45/47

See similar equations:

| 7(n+3)=77 | | 5x-15=6x-7 | | 5x=-3x-16 | | -8=-6+x/3 | | 6(h-86)=66 | | 7x-3=3x-4 | | 2/3x-20=40 | | -2m+3=21 | | 2c-7=c^2-9 | | X+4-(30/x^2)=0 | | 4^(2n)=16^n | | c-9-3=7c-12 | | y=4* | | 5(3x-2)+18=43 | | 384a^2-294=0 | | 2x-4/3x-6=2/3 | | 1/8y-2/3=51/2 | | 2x-4/3x-6=2/5 | | 15d+28d+18d=300 | | 12=10z-6z | | 2n^-2+17n^-1+18=0 | | 7/(x+1)-3/(x-1)=5x/x^2-1 | | 3=7+√5x+6 | | -11+10x+11-33=x+2x100 | | 7+4x/3-12=-3 | | 6x-9=7×+7 | | 7x+7=10×-38 | | x-3=+3-x | | 16r+2r^2=54 | | 2(2y-1)=-10 | | (6-z)(3z-1)=0 | | e/15=15 |

Equations solver categories